Analysis on smoking cessation rate among patients in Hospital Sultan Ismail, Johor / Siti Mariam Norrulashikin - Norrulashikin, Siti Mariam; Puslan, Ruzaini Zulhusni; Kamisan, Nur Arina Bazilah; Mohd Nor, Siti Rohani (2021)
Smoking is one of the most common unhealthy habits, with widespread health impacts. Based on the National Cancer Institute Dictionary of Cancer Terms, a person can reduce the risk of serious health problems by quitting smoking. Smoking Cessation Clinic (SCC) is an outpatient clinic available for smokers that need assistance in stopping smoking. Therapeutic supports such as counselling, behavior therapy and drugs may help someone stop smoking. The purpose of this study is therefore to descriptively examine demographic characteristics and to identify factors that influence smoking cessation among patients. Logistic regression is used in the current analysis, since this model is the most appropriate for analyzing numerical and categorical data. This model illustrates how one or more independent variables are linked to a dependent variable. The result of this analysis would provide us with two potential outcomes: smoking success versus smoking failure. The data of patients is collected from Hospital Sultan Ismail Johor Bahru (HSIJB) research center, and from the results, we found that method of quitting smoking and degree of addiction have a major impact on how effective patients are in quitting smoking. Predicting variables that will affect a smoker's chances of quitting is useful in designing and procuring lifesaving drugs. This would reduce the risk of deaths in patients that were caused by their smoking behaviour.